Integration of financial feasibility analysis and performance index in medium-scale semi-closed house broiler chicken businesses - Hana Nur Eritrina; Salsabila Imtaza (Privietlab, 2026)
The development of semi-closed housing systems has become an alternative transition between open and fully closed housing in medium-scale broiler chicken production. However, empirical studies integrating technical performance and financial feasibility of this system are still limited. This study aims to analyse the feasibility of broiler chicken farming using the semi-closed house system through an integrated approach between financial analysis and Performance Index (PI) in one production period. The study was conducted at the Lancar Jaya Farm in Malang Regency, with a population of 6,900 broiler chickens. Quantitative data, including fixed costs, variable costs, revenue, and production performance parameters, were analyzed descriptively using profit indicators, the R/C ratio, BEP, and PI. The results showed that the business generated a profit of IDR 27,178,137 per production period, with an R/C ratio of 1.1 and a PI of 359, which are above the national standard. These findings indicate that the semi-closed house system is capable of achieving efficient technical and financial performance on medium-scale farms. This study provides empirical contributions as a reference for farmers’ decision-making in optimizing broiler chicken housing systems and production management.